Learning Vocabulary through Colorful Pictures: An Experimental Research on Tenth-Grade Students of SMKN 2 Mataram in the Academic Year 2024/2025 - Ramandhani, Icha; Amrullah; Melani, Boniesta Zulandha (LITPAM, 2026)
This study aims to investigate the effectiveness of colorful pictures as an instructional medium for improving English vocabulary achievement among tenth-grade students at SMKN 2 Mataram in the academic year 2024/2025. Employing a pre-experimental one-group pretest-posttest design, this study included 30 students as the sample. Data were collected through vocabulary tests administered before and after treatment using colorful pictures. The Shapiro-Wilk normality test confirmed non-normal distribution (p < 0.05 for both pre-test and post-test). Due to the non-normal distribution of the data, as confirmed by the Shapiro-Wilk test, the Wilcoxon Signed-Rank Test was used for statistical analysis. The pre-test mean score was 7.42 (SD = 1.27), while the post-test mean score significantly improved to 8.99 (SD = 1.16), yielding a gain score of 1.57. The Wilcoxon Signed-Rank Test produced T+ = 435, which exceeded the critical value of 147 at α = 0.05, with p-value < 0.001. These results indicate that the null hypothesis is rejected and the alternative hypothesis is accepted, confirming that colorful pictures significantly improve students' vocabulary achievement. Brief practical implications suggest that this strategy is accessible, low-cost, and engaging for SMK contexts. The findings support Dual Coding Theory, which posits that simultaneous verbal and visual encoding enhances memory retention. This study contributes empirical evidence that colorful pictures are an effective, accessible, and engaging instructional strategy for vocabulary teaching in Indonesian vocational high school (SMK) contexts.